2016
DOI: 10.1080/14992027.2016.1225991
|View full text |Cite
|
Sign up to set email alerts
|

Functional hearing in the classroom: assistive listening devices for students with hearing impairment in a mainstream school setting

Abstract: Speech recognition improvements were demonstrated with the implementation of both remote microphones and soundfield systems. Both students and teachers reported functional hearing advantages in the classroom when using the remote microphone in concert with their standard hearing devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
4
15
0
1
Order By: Relevance
“…However, in many cases, especially for teenagers, as previous studies have shown, despite the perceptual benefit of the device, a higher role in the device uptake as well as acceptance and usage is played by personal and environmental factors (stigma, low self-esteem, cosmetic appearance, self-perception of normality). One of the most significant barriers is the social factor, specifically, not wanting to appear different from their peers [ 2 , 9 , 29 ]. Taking these factors into consideration may contribute to motivating children to use RM regularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in many cases, especially for teenagers, as previous studies have shown, despite the perceptual benefit of the device, a higher role in the device uptake as well as acceptance and usage is played by personal and environmental factors (stigma, low self-esteem, cosmetic appearance, self-perception of normality). One of the most significant barriers is the social factor, specifically, not wanting to appear different from their peers [ 2 , 9 , 29 ]. Taking these factors into consideration may contribute to motivating children to use RM regularly.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the use of primary compensatory devices (hearing aids/cochlear implants), children who are hard of hearing (HoH) are disadvantaged compared to their peers. These disadvantages include speech recognition under noisy conditions or understanding speech at a greater distance [ 1 , 2 , 3 ]. This do not necessarily mean that the child cannot hear or understand, but they usually find listening more difficult and have to exert more effort than their classmates with normal hearing [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Limited communication with the environment due to hearing impairment often leads to the isolation of the individual from society. The value of hearing for the development of an individual can only be realised when the functionality of the hearing organ is reduced or the hearing is completely lost (Zanin & Rance, 2016). It is stated that the concepts of hearing impairment and hearing impairment are used synonymously.…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
“…During the mainstream class, provision of more details or extra explanation and visual clarification during teaching can be used as an additional support for children with a hearing impairment (Bamu et al, 2017). Zanin and Rance (2016) have proved that assistive technologies (for example, remote microphones and remote loudspeakers) in a classroom can be very helpful for improving listening and communication skills with children with hearing impairments (Zanin & Rance, 2016), which increases the chances of their academic and social inclusion. Also, the awareness of a child's hearing impairment among the hearing children and teachers can promote the social inclusion of children with hearing impairments (Hadjikakou et al, 2008).…”
Section: Children With a Hearing Impairment In A Mainstream Schoolmentioning
confidence: 99%